Assessment of agricultural land carrying capacity for food availability in Situbondo Regency, Indonesia - Rois Dinan (Jurnal Ilmiah Pertanian, 2023)
The decline in food crop production indicates a region's declining level of food security. One of the factors is caused by a decrease in the quantity and physical quality of the agricultural environment. In the last five years, Situbondo Regency has experienced a reduction in rice production by 40%. This massive decline indicates the importance of testing the carrying capacity of agricultural land in Situbondo Regency. This study aimed to identify agricultural land's capability in producing rice as a staple food crop in Situbondo Regency. This study used the land suitability assessment method for rice plants based on physical and environmental variables. After that, the rice produced from agricultural land would be calculated by calculating the amount of land with high suitability and the average rice production in Situbondo Regency. The identification results showed that the Situbondo Regency could produce 169,642 tons of food in the existing conditions. With a moderate amount of food consumption of 57,822 tons per capita per year, food availability was at a surplus of 111,761 tons. Therefore, it could be input for relevant stakeholders, especially for the Food Security Agency, in formulating policies related to the provision of food for the people of Situbondo Regency. So from now on, the efforts to diversify food and protect productive land can be achieved relatively quickly.